Implementasi Model Pembelajaran STAD Untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Materi Kasifikasi Makhluk Hidup - Aang Zenal Mutakin (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2022)
The low activity and learning outcomes in science in class VII-B MTsN-2 Pangandaran prompted this study. The purpose of this study was to increase the activities and results of learning science in the material Classification of Living Things for class VII-B students of MTSN 2 Pangandaran for the 2019/2020 academic year through the implementation of the STAD learning model. The method used in this research is classroom action research, which consists of two cycles. Each cycle consists of two meetings with four stages: planning, implementing, observing, and reflecting. The data analyzed in this study are quantitative and qualitative. Quantitative data is in the form of student performance scores through discussions, simulations, and group demonstrations. Qualitative data in the form of recorded information on student activity and involvement during the learning process The results of the research show that there is an increase in the average and percentage of student learning outcomes. In the pre-cycle, the average value was only 58.14, with 39.29% completeness. In cycle I, the average score increased to 64.71 with a completeness percentage of 64.29%, and in cycle II, the average score increased to 76.11 with a completeness percentage of 92.86%. The percentage of student learning activities in the first cycle was 82.22%, and in the second cycle, the percentage increased to 84.29%. This proves that the implementation of the STAD cooperative learning model can increase student learning activities.